80.6k views
3 votes
What is the solution to the equation below?A.x = -B.x = C.x = 2D.x = 16

What is the solution to the equation below?A.x = -B.x = C.x = 2D.x = 16-example-1
User Hexodus
by
6.0k points

1 Answer

0 votes

The given equation is

4 + √(6x + 4) = 8

Subtracting 4 from both sides, it becomes

4 - 4 + √(6x + 4) = 8 - 4

√(6x + 4) = 4

Square both sides. It becomes

[√(6x + 4)]^2 = 4^2

6x + 4 = 16

Subtracting 4 from both sides, it becomes

6x + 4 - 4 = 16 - 4

6x = 12

Dividing both sides by 6,

6x/6 = 12/6

x = 2

User Steve Vaughan
by
5.8k points